Correlation between Cornification of Vaginal Epithelial Cells and Serum Progesterone Concentration during Proestrus and Estrus in She-Dogs - Sharma, Ananya; Singh, Madhumeet; Sharma , Akshay (The Indian Journal of Animal Reproduction, 2022)
The present study was conducted on fifteen she-dogs presented to the Department of Veterinary Gynaecology and Obstetrics, CSK Himachal Pradesh Krishi Vishvavidyalaya (CSKHPKV), Palampur for determination of mating time. Serum progesterone was estimated from the blood sample collected in the clot activator by cephalic venepuncture from she-dogs during the proestrus and estrus stages. The objective of the study was to establish a correlation between epithelial cells proportion (%) in vaginal epithelium with serum progesterone concentration (ng/mL) during proestrus, early estrus, and mid to late estrus in she-dogs. A significant positive correlation (r= 0.74; p0.05) for non-cornified cells (r= -0.7408 to -0.5807). Also, the cornified cell proportion was significantly higher (p
Keywords: Cornified cells; Linear correlation and regression; Reproduction; Serum progesterone; She-dogs